2004
DOI: 10.1002/masy.200450903
|View full text |Cite
|
Sign up to set email alerts
|

Recent data on the number of active centers and propagation rate constants in olefin polymerization with supported ZN catalysts

Abstract: Data on the number of active centers (Cp) and propagation rate constants (Kp) have been obtained by means of polymerization quenching with 14CO of propylene and ethylene polymerization with supported titanium‐magnesium catalysts (TMC) with different composition. In the case of propylene polymerization the Cp and Kp values have been measured separately for isospecific, aspecific and low stereospecific centers. Effects of MgCl2 support, internal and external donors are discussed on the basis of data obtained.Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 0 publications
2
34
0
Order By: Relevance
“…As compared to the data reported in literatures for ethylene and propylene homopolymerizations with similar supported ZN catalysts, the initial values of k pE and k pP reported in this work are similar to those reported by Zakharov et al 33 but evidently lower than those reported by Terano and coworkers 34 The ratio of k pE /k pP was the highest in the first 30 s, and then decreased with time. As compared to the data reported in literatures for ethylene and propylene homopolymerizations with similar supported ZN catalysts, the initial values of k pE and k pP reported in this work are similar to those reported by Zakharov et al 33 but evidently lower than those reported by Terano and coworkers 34 The ratio of k pE /k pP was the highest in the first 30 s, and then decreased with time.…”
Section: Rate Constantssupporting
confidence: 89%
“…As compared to the data reported in literatures for ethylene and propylene homopolymerizations with similar supported ZN catalysts, the initial values of k pE and k pP reported in this work are similar to those reported by Zakharov et al 33 but evidently lower than those reported by Terano and coworkers 34 The ratio of k pE /k pP was the highest in the first 30 s, and then decreased with time. As compared to the data reported in literatures for ethylene and propylene homopolymerizations with similar supported ZN catalysts, the initial values of k pE and k pP reported in this work are similar to those reported by Zakharov et al 33 but evidently lower than those reported by Terano and coworkers 34 The ratio of k pE /k pP was the highest in the first 30 s, and then decreased with time.…”
Section: Rate Constantssupporting
confidence: 89%
“…The ratios between the rate constant of chain transfer to comonomer and the propagation rate constant for propylene ( k trPr) and 1‐hexene ( k trHex) are equal to 1.7 × 10 −4 and 4.4 × 10 −5 , respectively. It was found in Ref 28. that k p upon ethylene polymerization on TMC is equal to 1.2 × 10 4 L mol −1 s −1 .…”
Section: Resultsmentioning
confidence: 95%
“…They are somewhat higher than that of the TiCl 4 /MgCl 2 -AlEt 3 catalyst (12 000 L Á (mol Á s) À1 at 70 8C). [22] Effect of Support on the Number of Active Centers, Propagation Rate Constant and PE Molecular Mass and MMD According to the data in ref. [7] homogeneous LFeCl 2 -MAO and LFeCl 2 -AlR 3 catalysts are almost inactive at elevated polymerization temperatures (!50 8C).…”
Section: Effect Of Hydrogen On the Number Of Active Centers And Propamentioning
confidence: 99%